The relationship between the locus of control, coping strategies and procrastination among undergraduates in Malaysia - Ang, Hui Qin; Chan, Siew Man; Wong, Ee Leng (2020)
Procrastination is a popular issue and has become an increasingly serious problem nowadays especially among the undergraduate students in Malaysia. The present study was aimed to explore the relationship between LOC, coping strategies such as problem solving, avoidance, positive thinking, and social support, as well as procrastination. This current study is also determined how the variables of LOC and coping strategies predict procrastination. A total of 150 participants were recruited through convenience sampling in UTAR, Kampar campus. This study was a quantitative and cross-sectional study. Data was collected by using the paper-and-pencil method. The Internal and External Locus of Control (Rotter, 1996), Brief COPE (Carver, 1997), Tuckman Procrastination Scale (Tuckman, 1991) were used as the measurements of this study. Results of Pearson Correlation depicted that there was no significant correlation between LOC and coping strategies, significant negative correlation between problem solving coping strategy and procrastination, significant positive correlation between avoidance coping strategy and procrastination while no significant correlation between positive thinking and social support coping strategies with procrastination. The result also showed that there was significant positive correlation between LOC and procrastination. Besides, the results of Stepwise Multiple Regression indicated that LOC predicted procrastination. However, LOC was unable to predict procrastination when there was presence of problem solving and avoidance coping strategies whereas these two strategies were able to predict procrastination. Implications and limitations of this research have been discussed and recommendations have been made for further research.